FACTORS THAT INFLUENCE ICT INFRASTRUCTURE IN HIGHER EDUCATION: A CASE STUDY - Miseviciene, Regina; Sutiene, Kristina; Ambraziene, Danute; Makackas, Dalius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article analyses essential factors that can affect the Information and Communication Technology (ICT) infrastructure in higher education. There is a general lack of research on providing the general criteria for infrastructure that could be used as guidelines for education institutions. Higher schools usually develop their own infrastructure based on experts’ advice or delegate this task to the private IT companies. The article aims to investigate how users’ demands influence higher education ICT infrastructure. Therefore, the university-wide students’ demands that affect not only their academic performance but also particular activities are epitomized in the paper. As a case study, the ICT infrastructure of Kaunas University of Technology (KUT) was investigated in order to determine how university e-services fulfil the students’ demands. The research showed that some KUT e-services comply with specific students’ demands, while the others are universal and widely applicable. On closer inspection, it was inferred that not all demands are supported by e-services in the university as only the general information about a particular service is provided.